Artykuł oryginalnyA three-dimensional analysis of jejunal myenteric ganglia: a tool for interpretation of the optical recording - Ceregrzyn, Michał; Woliński, Jarosław; Kuch, Birgit (Archives of Medical Science, 2006)
Introduction: Investigating functions of neurons in the enteric nervous system using imaging techniques (e.g. voltage sensitive dyes) requires precise data concerning the three-dimensional structure of enteric ganglia. Recording from small enteric ganglia such as the submucosal plexus allows for single cell resolution recording, while myenteric ganglia are more complex and single cell resolution claim is not straightforward. Therefore, the aim of the present study was to analyze appositions of neuronal somata in myenteric ganglia. Material and methods: Stretched samples of guinea pig jejunum were fixed and dissected to expose the myenteric plexus. Tissues were stained for Hu protein and confocal microscopic analysis of myenteric ganglia was performed in order to reconstruct three-dimensional allocations of neuronal somata within the myenteric plexuses. Results: Myenteric neurons form a three-dimensional structure. Analysis of 103 cells showed that 20% were not overlapping with other cells, while 30% and 31% overlapped with 1 and 2 cells, respectively. Looking at the area of overlap, 42% of cells shared less than 10% of their area. On the other hand, 17% of cells had more than 50% of their area shared with others. Conclusions: These results show that in guinea pig myenteric ganglia neuronal somata form a monolayer, but up to half of the cells may have a significant overlap with other cell somata. Therefore all optical studies claiming single cell resolution recorded from the myenteric plexus should be confirmed by confocal analysis of the ganglia using immunohistochemical identification of cellular structure of analyzed plexuses.